Clinical outcomes and patterns of population‐based management of urachal carcinoma of the bladder: An analysis of the National Cancer Database. (4th May 2022) - Dursun, Furkan; Lim, Kelvin; Svatek, Robert S.; Xu, Jiaqiong; El‐Zaatari, Ziad M.; Wenker, Evan P.; Klaassen, Zachary W.; Mansour, Ahmed M.; Muhammad, Taliah; Efstathiou, Eleni; Sonpavde, Guru P.; Wallis, Christopher J. D.; et al.
Abstract: Background: Given the low incidence of urachal carcinoma of the bladder (UCB), there is limited published data from contemporary population‐based cohorts. This study aimed to describe demographic, clinicopathological features, and survival outcomes of patients diagnosed with UCB. Methods: The National Cancer Database (2004–2016) was queried for UCB patients. Descriptive analyses characterized demographics and clinicopathologic features. We assessed 5‐year overall survival (OS) rates of the entire cohort and subgroups of localized/locally advanced and metastatic disease. We utilized Cox proportional hazards models to assess the association between covariates of interest and all‐cause mortality and to examine the impact of surgical technique and chemotherapy. Results: We identified 841 patients with UCB. The most common histologic subtype was non‐mucinous adenocarcinoma (39.6%). Approximately 50% had ≥cT2 disease, and 14.3% were metastatic at diagnosis. Altogether, partial cystectomy (60%) was most performed, and lymph node dissection was performed in 377 patients (44.8%), with specific temporal increase in utilization over the study period ( p  < 0.001). Overall, median OS was 59 months, and 5‐year OS was 49%. In patients with localized/locally advanced disease, we found no association between partial and radical cystectomy (Hazards ratio [HR] 1.75; 95% CI 0.72–4.3) as well as receipt of perioperative chemotherapy (HR 1.97, 95% CI 0.79–4.90) and outcomes. Lastly, receipt of systemic therapy was not associated with survival benefit (HR 0.785, 95% CI 0.37–1.65) in metastatic disease cohort. Conclusion: This large population‐based cohort provides insight into the surgical management and systemic therapy, without clear evidence on the association of chemotherapy and survival in the perioperative and metastatic setting. Abstract : This large population‐based cohort of urachal carcinoma of the bladder (UCB) provides insight into the surgical management and systemic therapy, without clear evidence on the association of chemotherapy and survival in the peri‐operative and metastatic setting. Prospective, multi‐intuitional studies are needed to identify multi‐modal approaches to improve outcomes for patients with UCB.